The Values of Character Education in the Origin of Lampung Folklore: A Study of Literary Sociology - Rahmawati, Lenny; Fuad, Muhammad; Suyanto, Edi (Graduate Program Magister Manajemen Pendidikan, 2022)
This study seeks to identify and describe the character education contained in the story of Origins of Lampung. By utilizing the Lampung Origin Story as a source of research data, a qualitative descriptive methodology was used. Data analysis was carried out using content analysis techniques. Based on the analysis of the Lampung Origin story, six values of character education have been identified. Tolerance, independence, curiosity, friendly or communicative, social care, and responsibility are the values of character education. These values are the basis for the idea that folklore is not only used to introduce stories that were believed by the ancestors, but also can be used as a means of character education.